Kondisi Keluarga yang Mengalami Strees dan Bentuk Penanggulangan sebagai Stress yang Positif - Farah Rizkita Putri (JURNAL LENTERA ANAK, 2020)
The phenomenon seen at research before explain that there are some factors which stress influence until stress child experience after age low. Stress influence which happened come about by architecture inside child’s brain which work out while their experience. Stress obviously be divided as two parts are positive stress and negative stress. Factors that underlie the child can experience stress is their nearest environment are father, mother and brother or sister. These three factors encourage the level of child experience stress increasingly too if found their parents work and then left them with baby sitter. Afterwards effect toward child who stress after and it is called posttraumatic stress disorder (PTSD)this is indicating would influence raising child experience stress and decrease aspect of development who happened it. The countermeasure of stress is themselves that is change negative stress to be positive stress.